Farm buildings for Kansas - Ross, John F. (My University, 1902)
Introduction: This subject can be treated in a general way only in a paper of this kind. No hard and fast rules can be laid down to be followed by all farmers in all parts of the State. Nevertheless there are a few principles that must be considered before the buildings are begun. The very first thing to be considered is the location of the buildings on the farm, i.e. site or building place. This position cannot be decided upon without taking into account the shape of the farm, the nature of the ground, the lay of the land and its position in relation to the public road. In order that all fields shall be easily reached these buildings should have central position on the farm but should not be in the exact center for that would be too far back from the road. If there is a place slightly elevated above the surrounding fields, so much the better, as it will make the subject of drainage much more simple. Good drainage is one of the prime requisites in keeping the buildings, yards and grounds in proper condition. Nothing lens so much to the appearance of buildings, health of animals and the contentment of those who do the work as clean, well-drained grounds and yards. Muddy yards covered with trash are sights which will tempt some of the best of boys to leave the farm in sheer disgust. If there is little natural drainage the only thing to do is to put in artificial drainage.
Citation: Ross, John F. Farm buildings for Kansas. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Farm Buildings; Architecture; Kansas; Building Site; Theses